(untitled) (Ustozlar uchun, 2025)
This thesis explores major environmental problems and their connection to climate change. Human activities, such as industrial emissions, deforestation, urbanization, and excessive use of fossil fuels, have significantly contributed to air and water pollution, soil degradation, and biodiversity loss. These environmental issues exacerbate global warming, leading to rising temperatures, extreme weather events, sea-level rise, and ecosystem disruptions. The research highlights key challenges, including plastic pollution, eutrophication, overfishing, and ocean warming, and discusses their impact on both natural and human systems. Addressing these issues requires urgent global cooperation, sustainable resource management, and reduction of greenhouse gas emissions to protect the planet and future generations.